Scientific Opinion on the substantiation of health claims related to alpha cyclodextrin and reduction of post prandial glycaemic responses (ID 2926, further assessment) pursuant to Article 13(1) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to provide a scientific opinion on a health claim pursuant to Article 13.1 of Regulation (EC) No 1924/2006 in the framework of further assessment related to alpha‐cyclodextrin and reduction of post‐prandial glycaemic responses. The food constituent that is the subject of the claim, alpha‐cyclodextrin, is sufficiently characterised. The claimed effect, reduction of post‐prandial glycaemic responses (as long as post‐prandial insulinaemic responses are not disproportionally increased), may be a beneficial physiological effect. The proposed target population is individuals who wish to reduce their post‐prandial glycaemic responses. In weighing the evidence, the Panel took into account that two intervention studies showed a significant effect of alpha‐cyclodextrin added to starch on post‐prandial glycaemic responses without disproportionally increasing post prandial insulinaemic responses, that one study on alpha‐cyclodextrin added to sucrose did not show an effect on post‐prandial glycaemic responses, and that there is some evidence in support of a plausible mechanism by which alpha‐cyclodextrin could exert the claimed effect. On the basis of the data presented, the Panel concludes that a cause and effect relationship has been established between the consumption of alpha‐cyclodextrin with starch containing meals and reduction of post‐prandial glycaemic responses. The Panel considers that in order to obtain the claimed effect, at least 5 g of alpha‐cyclodextrin per 50 g of starch should be consumed. The target population is adults who wish to reduce their post‐prandial glycaemic responses.